Against the odds - Layden, Joseph, 1959- (New York : Scholastic, 1997)
Contains stories that provide information about the personal struggles and triumphs of eight NBA players, including Nick Anderson, Chris Gatling, Steve Kerr, Reggie Miller, Alonzo Mourning, Chris Mullin, Carlos Rogers, and Jayson Williams.
6.7
3-6
Keywords: Basketball players -- United States -- Biography -- Juvenile literature; Basketball players; Basketball players -- Biography